Presenting symptoms and time to diagnosis for Pediatric Central Nervous System Tumors in Qatar: a report from Pediatric Neuro-Oncology Service in Qatar - Ata U. R. Maaz (14150490) (2020)
Introduction There are no previous published reports on primary pediatric tumors of the central nervous system (CNS) in Qatar. We undertook this retrospective cohort study to review the diagnosis of CNS tumors in children in Qatar to analyze the presentation characteristics including symptoms, referral pathways, and time to diagnosis. Methods All children registered with Pediatric Neuro-Oncology service (PNOS) were included in the study. Data from the time of diagnosis (October 2007 to February 2020) were reviewed retrospectively. Presenting symptoms were recorded and pre-diagnosis symptom interval (PSI) was calculated from the onset of the first symptom to the date of diagnostic imaging. Results Of the 61 children registered with PNOS during the study period, 51 were included in the final analysis. Ten children were excluded because they were either diagnosed outside Qatar (n = 7) or were asymptomatic at the time of diagnosis (n = 3). The median age was 45 (range 1–171) months. Common tumor types included low-grade glioma (LGG) (47.1%) and medulloblastoma/primitive neuro-ectodermal tumors (PNET) (23.5%). Nine children had an underlying neurocutaneous syndrome. Thirty-eight patients (74.5%) had at least one previous contact with healthcare (HC) professional, but 27 (52%) were still diagnosed through the emergency department (ED). Presenting symptoms included headache, vomiting (36.2%), oculo-visual symptoms (20.6%), motor weakness (18.9%), seizures, ataxia (17.2% each), irritability, cranial nerve palsies (12% each), and endocrine symptoms (10.3%). Median PSI was 28 days (range 1–845 days) for all CNS tumors. Longest PSI was seen with germ cell tumors (median 146 days), supratentorial location (39 days), and age above 3 years (30 days). Tumor characteristics of biological behavior (high-grade tumor) and location (infratentorial) were significantly associated with shorter PSI, as were presenting symptoms of ataxia, head tilt, and altered consciousness. Conclusions Although overall diagnostic times were acceptable, some tumor types were diagnosed after a significant delay. The awareness campaign, such as the “HeadSmart” campaign in the United Kingdom (UK), can improve diagnostic times in Qatar. Further research is required to better understand the reasons for the delay. Other Information Published in: Child's Nervous System License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s00381-020-04815-z